THE TAX PAYMENT SYSTEM: MECHANISMS AND OPERATIONAL PRACTICE (International journal of artificial intelligence, 2026)
This article examines the modern mechanisms and operational practices of tax payment systems in the context of global digitalization. It analyzes the transition from traditional bureaucratic procedures to automated "TaxTech" ecosystems, emphasizing the role of real-time data processing and electronic invoicing. The study explores how integrated digital platforms reduce administrative burdens, minimize the "tax gap," and enhance voluntary compliance through increased transparency. Furthermore, the paper discusses the impact of artificial intelligence and predictive analytics on risk management and tax auditing. The findings suggest that the efficiency of a fiscal system depends on its technical accessibility and the interoperability of digital infrastructure.